The success factors in Government Information Sharing (GIS) - empirical findings from the Malaysian’s natural disaster management context - Ahmad Dahlan, Abdul Rahman; Mohd Dahan, Hayati; Mohd Saman, Md Yazid (IEEE, 2014)
Governments around the world are turning to information sharing and collaboration in an interactive process to act on issues such as natural disasters. This demand for a comprehensive disaster management (DM) program covering a wide range of disciplines, sectors and organizations, calling for diverse and expanded forms of collaboration can be far more powerful than individual contributions. The occurrences of natural disasters has been increasing for the last 30 years in the world causing great damages and losses, where about 90% are concentrated in the Asian region. Malaysia has also experienced some devastating natural disasters. In 2007, 29 people had been killed and more than 166,000 people had been affected by floods, with economic damage amounting to USD 968 million. DM including disaster risk reduction (DRR)efforts aim to minimize or avoid the potential losses from hazards, assure prompt and appropriate assistance to victims of disaster, and achieve rapid and effective recovery. While data, information, knowledge, experiences, expertise and resources sharing can enhance the process of DM, there is a perceived gap in government collaboration and coordination within the context of natural DM. The objective of this paper is to present the initial empirical findings on the success factors that can provide high quality of government information sharing (GIS) in supporting effectively DM in Malaysia.